Prevalence of Asthma and Risk Factors for Asthma-Like Symptoms in Aboriginal and Non-Aboriginal Children in the Northern Territories of Canada. Issue 3 (2008) - Gao, Zhiwei; Rowe, Brian H; Majaesic, Carina; O'Hara, Cindy; Senthilselvan, A
Abstract : BACKGROUND: Few studies have investigated the prevalence and risk factors of asthma in Canadian Aboriginal children. OBJECTIVE: To determine the prevalence of asthma and asthma-like symptoms, as well as the risk factors for asthma-like symptoms, in Aboriginal and non-Aboriginal children living in the northern territories of Canada. METHODS: Data on 2404 children, aged between 0 and 11 years, who participated in the North component of the National Longitudinal Survey of Children and Youth were used in the present study. A child was considered to have an asthma-like symptom if there was a report of ever having had asthma, asthma attacks or wheeze in the past 12 months. RESULTS: After excluding 59 children with missing information about race, 1399 children (59.7%) were of Aboriginal ancestry. The prevalence of asthma was significantly lower (P<0.05) in Aboriginal children (5.7%) than non-Aboriginal children (10.0%), while the prevalence of wheeze was similar between Aboriginal (15.0%) and non-Aboriginal (14.5%) children. In Aboriginal children, infants and toddlers had a significantly greater prevalence of asthma-like symptoms (30.0%) than preschool-aged children (21.5%) and school-aged children (11.5%). Childhood allergy and a mother's daily smoking habit were significant risk factors for asthma-like symptoms in both Aboriginal and non-Aboriginal children. In addition, infants and toddlers were at increased risk of asthma-like symptoms in Aboriginal children. In analyses restricted to specific outcomes, a mother's daily smoking habit was a significant risk factor for current wheeze in Aboriginal children and for ever having had asthma in non-Aboriginal children. CONCLUSIONS: Asthma prevalence appears to be lower in Aboriginal children than in non-Aboriginal children. The association between daily maternal smoking and asthma-like symptoms, which has been mainly reported for children living in urban areas, was observed in Aboriginal and non-Aboriginal children living in northern and remote communities in Canada.